2011
DOI: 10.1002/chem.201003275
|View full text |Cite
|
Sign up to set email alerts
|

Azobenzene‐Based Colorimetric Chemosensors for Rapid Naked‐Eye Detection of Mercury(II)

Abstract: Two new highly selective colorimetric chemosensors for Hg(2+), based on azobenzene and highly selective Hg(2+)-promoted deprotection of a dithioacetal have been designed and synthesized. In the presence of as little as 20 μM Hg(2+), the sensors change their color from light yellow to deep red, which can easily be observed by the naked eye. The underlying signaling mechanism is intramolecular charge transfer (ICT). The sensors have good selectivity for Hg(2+) with respect to several common alkali, alkaline eart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
56
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(56 citation statements)
references
References 100 publications
0
56
0
Order By: Relevance
“…Hence, it is imperative to screen suitable Hg 2+ detection systems with high selectivity, sensitivity and reliability. Many methods have been developed specifically for Hg 2+ ion detection (Coronado et al, 2005;Kim et al, 2010Kim et al, , 2012Misra & Shahid, 2010;Cheng et al, 2011;Dalapati et al, 2011;Tian & Ihmels, 2011;Ren et al, 2012;Chen et al, 2013;Goswami et al, 2013;Lu et al, 2013;Madhu et al, 2013;Shafeekh et al, 2013;Bera et al, 2014;Carter et al, 2014;Huang et al, 2014;Li et al, 2014;Thirupathi et al, 2014). For example, Thirupathi et al (2014) reported a ratiometric fluorescence chemosensor based on tyrosine derivatives for monitoring mercury ions in aqueous solutions.…”
Section: Introductionmentioning
confidence: 98%
“…Hence, it is imperative to screen suitable Hg 2+ detection systems with high selectivity, sensitivity and reliability. Many methods have been developed specifically for Hg 2+ ion detection (Coronado et al, 2005;Kim et al, 2010Kim et al, , 2012Misra & Shahid, 2010;Cheng et al, 2011;Dalapati et al, 2011;Tian & Ihmels, 2011;Ren et al, 2012;Chen et al, 2013;Goswami et al, 2013;Lu et al, 2013;Madhu et al, 2013;Shafeekh et al, 2013;Bera et al, 2014;Carter et al, 2014;Huang et al, 2014;Li et al, 2014;Thirupathi et al, 2014). For example, Thirupathi et al (2014) reported a ratiometric fluorescence chemosensor based on tyrosine derivatives for monitoring mercury ions in aqueous solutions.…”
Section: Introductionmentioning
confidence: 98%
“…They are the main class of all synthetic dyes that are widely used in the world 22 . The importance of azo dyes returns to their significant physicochemical features such as stability 23 , optical properties 24,25 and their extensive applications in chemosensors 26,27 , liquid crystals 28 and nanotubes 29 .…”
Section: Introductionmentioning
confidence: 99%
“…Based on the mercury(II)-promoted thioacetal deprotection, several Hg 2+ detection assays have been reported [27,28,29,30,31,32,33]. Zhen Li’s group developed an ethylthio-posessing, azobenzene- or triphenylamine-based chemosensor for Hg 2+ detection, utilizing intramolecular charge transfer (ICT) as a sensory mechanism [30,31]. In the presence of Hg 2+ , electron donating alkylthioacetal groups were converted to an electron-withdrawing aldehyde group, resulting in changes in ICT interaction through the molecule.…”
Section: Introductionmentioning
confidence: 99%
“…By differentiating the electron donating groups, the sensitivity of the sensor system was successfully modulated, showing a 10–400 nM limit of detection (LOD). However, most previous Hg 2+ assays demonstrated Hg 2+ detection in organic solvents such as tetrahydrofuran (THF), MeOH, and mixed organic/water due to the poor water solubility of fluorescent probes [29,30,31,32,33]. Highly sensitive and selective Hg 2+ detection in aqueous media is urgently needed because mercury poisoning usually results from the exposure to water-soluble forms of mercury by inhalation and/or ingesting.…”
Section: Introductionmentioning
confidence: 99%